An approach to the management of children with problematic severe asthma - Fainardi, Valentina; Saglani, Sejal (Acta Biomedica Atenei Parmensis, 2020)
Children with poor asthma control despite high levels of prescribed treatment are described as having problematic severe asthma. Most of these children have steroid sensitive disease which improves with adherence to daily inhaled corticosteroids and after having removed modifiable factors like poor inhalation technique, persistent adverse environmental exposures and psychosocial factors. These children are described as having “difficult-to-treat asthma” while children with persistent symptoms despite above-mentioned factors having been addressed are described as having “severe therapy-resistant asthma”. In this review, we will describe the 6-step approach to the diagnosis and management of a child with problematic severe asthma adopted by The Royal Brompton Hospital (London, UK). The role of a multidisciplinary team is crucial for identification and treatment of modifiable factors and comorbidities in order to avoid invasive examinations and useless pharmacological treatments. The current knowledge on add-on therapies will be discussed.